The The Structure Analysis of Five Floor Mall Building in Semarang City According to SNI 1726-2019 and SNI 2847-2019 - Talitha Zhafira; Indra Bagus Kurniawan; Purwanto Purwanto; M Fahrul Hidayat; Hakas Prayuda (Journal of Civil Engineering and Planning (JCEP), 2023)
This structural planning of building that located in Mijen district is expected to became a practical economic center, complate, enjoy, and safety for society. The planning building based on Indonesian national standart regulation (SNI). SNI (2847-2019) â€œOn structural concrete requirements for the buildingsâ€ and SNI (1726-2019) â€œProcedures for planning and earthquake resistance for the building and non buildingâ€. For the planning is include of planning top and bottom structure that have a model of software ETABS 18 and Sp Column as a helper software. For the top structure it means include of the planning of roofs, beams, plat, column, and shearwall. Meanwhile the bottom structure it means include of foundations planning. This building is planned earthquake resistance based on earthquake data from website of Puskim-Kementrian PU. Based on the result of this structure is using double system with the special moment resisting frames and special slidding wall structural as a building earthquake resistance system. The result of this analysis is deviation between the floors direction X and Y is safety for service limit it, meanwhile for the analyse of vibration have fullfiled the rules. This is shows that the planning building can hold an earthquake resistance planning and had a good response during the earthquake.